Spatial distribution characteristics of splashing rainfall caused by nappe flow impingement on a plunge pool - Sun, Qian; Yuan, Hao; Wei, Wangru; Hu, Liangliang; Xie, Chunhang (Frontiers in Environmental Science, 2023)
Splashing is the main atomization source for a jet impinging on a liquid layer. Increased understanding of splashing rainfall characteristics can help to reduce the hazard of flood discharge atomization in hydraulic engineering. In this study, the spatial distribution of splashing rainfall caused by a nappe flow impinging on a downstream water cushion was experimentally investigated. Effects of the main hydraulic factors of impingement velocity, unit discharge, and water-cushion depth on splashing were investigated. The shape of splashing rainfall contours was approximately elliptical in horizontal planes. Maximum rainfall intensity was in the surrounding impingement region, and rainfall intensity decreased with an increase in the distance between the impingement center point and measurement points. Splashing rainfall intensity increased with increases in impingement velocity and unit discharge, whereas the opposite was observed with an increase in plunge pool depth. A gamma distribution described rainfall intensity distribution in the longitudinal and vertical direction, whereas a Gaussian distribution described intensity in the transverse direction. A series of empirical relations were proposed.